2007
DOI: 10.1177/154405910708600307
|View full text |Cite
|
Sign up to set email alerts
|

Microtensile Bond Strengths of Two Adhesive Resins to Discolored Dentin after Amalgam Removal

Abstract: Studies have reported the discoloration of dentin beneath amalgam restorations. The purpose of this study was to test the hypothesis that the bond strengths of adhesive resins to this discolored dentin are lower than those to normal dentin, and are related to the presence of metallic ions or corrosion products. Amalgam-filled extracted human teeth were used. After the removal of amalgam, the discolored dentin and surrounding normal dentin were bonded with Single Bond or Clearfil SE Bond and tested for microten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 20 publications
3
21
0
Order By: Relevance
“…Harnirattisai et al 9 found lower bond strengths to dark discoloured dentin after amalgam removal. Further studies will be required for developing clinical guidelines for adhesive restorative procedures on discoloured dentin after amalgam removal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Harnirattisai et al 9 found lower bond strengths to dark discoloured dentin after amalgam removal. Further studies will be required for developing clinical guidelines for adhesive restorative procedures on discoloured dentin after amalgam removal.…”
Section: Discussionmentioning
confidence: 99%
“…Harniratissai et al 9 For high-copper amalgams no further studies on the penetration of elements into dentin and only data from studies on marginal seals and corrosion phenomena of highcopper amalgams are available.…”
Section: Kurosaki and Fusayamamentioning
confidence: 99%
See 2 more Smart Citations
“…The resistance against initiation of crack growth and propagation depends on the geometry and the load configuration of the specimen. The use of the microtensile bond strength test to evaluate bond strength of adhesive systems has been widely accepted (18)(19)(20). Smaller specimens contain a lower number of initial defects and have more homogeneous stress distributions; hence, bond strengths as well as adhesive failure between the adhesive and dentin can be examined more accurately.…”
Section: Discussionmentioning
confidence: 99%